Interracial anatomical differences in the transsphenoidal approach to the sellar region - Dao Trong, Huy Philip; Jesser, Jessica; Schneider, Till M.; Unterberg, Andreas; Beynon, Christopher (British journal of neurosurgery, 2023)
Injury to vascular structures such as the internal carotid artery (ICA) is a rare but catastrophic complication of minimally invasive transsphenoidal surgery. Thorough preoperative planning, and knowledge of anatomical landmarks, such as the intercarotid distance (ICD) reduce this risk. Numerous anatomical studies have been conducted regarding the transsphenoidal approach, but none have taken racial disparities into account. Since differences of the cranium, especially of the skull base exist, we sought to analyze anatomical differences of the sellar region in thin sliced T2-weighted MRI scans of 187 (87 male and 100 female) Asian, African American and Caucasian patients provided by the ‘Human Connectome Project’ (HCP). We found significant differences in the ICD between males and females across all races. Furthermore, we found that the ICD was up to 2.4 mm smaller in the Caucasian cohort compared to the African American/Asian cohort. These findings indicate that racial disparities regarding the sellar anatomy should be considered in patients undergoing pituitary surgery.
"Published online: 14 Oct 2020".- Artikel-Front Door
Gesehen am 23.09.2024